2018
DOI: 10.1017/ppr.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

A Conservative Party? Pots and People in the Hebridean Neolithic

Abstract: Recent analysis of the ceramic assemblage from the Neolithic loch islet settlement of Eilean Dòmhnuill, North Uist, in the Western Isles of Scotland has highlighted the intense conservatism of the potting traditions over a period of more than 800 years. Hebridean Neolithic pottery exhibits clear relationships with pottery from Argyll, Arran, and Bute, as well as Orkney and the north-east mainland of Scotland. It appears to have developed a distinctive, often decoratively elaborate regional form very soon after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Armit has suggested, for example, that it may have been a place of special significance in the landscape, albeit one of impermanent occupation: its permanence, its monumentality, its peculiar location, and the repeated renewal of its buildings, combine to suggest that it played a pivotal role in the cultural landscape of Neolithic North Uist comparable with the role played by the better-known funerary monuments (Armit 2003: 99).Cummings and Richards (2013: 198–200) compared travelling to Eilean Domhnuill on a causeway across the water with the journey along the tunnel-like passageways of contemporaneous passage grave tombs; others have commented on the site's isolation and ‘liminal’ location (Henley 2003: 137; Cummings & Richards 2013). Most recently, Copper and Armit (2018)—now aware of the newly discovered Lewis islet sites—have suggested that they could have been special places associated with social gatherings, ritualised feasting and commensality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Armit has suggested, for example, that it may have been a place of special significance in the landscape, albeit one of impermanent occupation: its permanence, its monumentality, its peculiar location, and the repeated renewal of its buildings, combine to suggest that it played a pivotal role in the cultural landscape of Neolithic North Uist comparable with the role played by the better-known funerary monuments (Armit 2003: 99).Cummings and Richards (2013: 198–200) compared travelling to Eilean Domhnuill on a causeway across the water with the journey along the tunnel-like passageways of contemporaneous passage grave tombs; others have commented on the site's isolation and ‘liminal’ location (Henley 2003: 137; Cummings & Richards 2013). Most recently, Copper and Armit (2018)—now aware of the newly discovered Lewis islet sites—have suggested that they could have been special places associated with social gatherings, ritualised feasting and commensality.…”
Section: Discussionmentioning
confidence: 99%
“…Armit (1996) has suggested that architectural differences between sites may have been related to settlement function, with some occupied all year round and others only seasonally. Similarly, Henley (2003: 133) and Copper and Armit (2018) have observed that apparently contemporaneous sites produce very different ceramic assemblages, and that differences in social status and identity may explain this divergence in material culture.…”
Section: The Neolithic Of the Outer Hebridesmentioning
confidence: 96%
See 2 more Smart Citations
“…As bone does not survive well on the islands, this would almost certainly involve new excavation under modern conditions to obtain contextually secure young wood charcoal. Given the clear material links and thus presumed cultural connections between the Outer Hebrides and Orkney during the 4th millennium bc (expressed most clearly in the regions’ shared use of Unstan pottery), it is interesting to note the quite different archaeological records and chronologies of change associated with the earliest Neolithic in the two regions – connections around the western seaways may have existed, but they did not straightforwardly lead to similar trajectories of change (these are of course highly complex issues; see Copper 2015 for a more detailed discussion of the relationship between the Outer Hebrides and Orkney).…”
Section: Discussion: Understanding Process Appreciating Representatimentioning
confidence: 99%